2016
DOI: 10.5966/sctm.2015-0257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Induced Pluripotent Stem Cell Technology in Blood Banking

Abstract: SUMMARYPopulation aging has imposed cost-effective alternatives to blood donations. Artificial blood is still at the preliminary stages of development, and the need for viable cells seems unsurmountable. Because large numbers of viable cells must be promptly available for clinical use, stem cell technologies, expansion, and banking represent ideal tools to ensure a regular supply. Provided key donors can be identified, induced pluripotent stem cell (iPSC) technology could pave the way to a new era in transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Generation of immortalized erythroid cells able to proliferate indefinitely in an undifferentiated state whilst maintaining the capacity to undergo differentiation to generate reticulocytes has been a major goal of the erythroid biology field for decades. Early excitement surrounding the development of induced pluripotent stem cell lines has been tempered by the observation of severe erythroid differentiation defects, expression of fetal globins, and to date minimal capacity for enucleation 1012 . The capability of orthochromatic erythroblasts, characterized by their condensed nuclei, to support malaria parasite entry 13,14 has led to exploration of cell lines unable to complete differentiation as a model for invasion 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Generation of immortalized erythroid cells able to proliferate indefinitely in an undifferentiated state whilst maintaining the capacity to undergo differentiation to generate reticulocytes has been a major goal of the erythroid biology field for decades. Early excitement surrounding the development of induced pluripotent stem cell lines has been tempered by the observation of severe erythroid differentiation defects, expression of fetal globins, and to date minimal capacity for enucleation 1012 . The capability of orthochromatic erythroblasts, characterized by their condensed nuclei, to support malaria parasite entry 13,14 has led to exploration of cell lines unable to complete differentiation as a model for invasion 15 .…”
Section: Introductionmentioning
confidence: 99%
“…IPs-derived, pathogen-free, autologous or universal blood carries the potential to alleviate or eliminate the allogeneic blood shortages [ 25 ]. Small-scale bioreactors with disposable kits currently allow for in-hospital expansion of suspension cell cultures [ 26 ]; on an industrial scale, large-scale bioreactors would allow bulk production of iPS cells in desired amounts and potentially with no Hayflick limit.…”
Section: Ips Cells Technologymentioning
confidence: 99%
“…In the proper therapeutic niche, iPSC-RBCs would be high-value products due to their unique characteristics and the potential to alleviate shortages of specific RBC products. 28 Here, we tested the effect of human platelet lysate (hPL) on the maturation of iPSC-RBCs, and investigated the in vivo behavior of the resulting iPSC-RBCs in the immunodeficient NOD scid gamma (NSG) mouse model. We also showed that iPSC homed to the bone marrow and continue development to mature RBCs, suggesting that this may represent a useful in vivo model to better understand the mechanisms directing erythroblasts to differentiate into mature RBCs.…”
Section: Introductionmentioning
confidence: 99%